Comparison of effect of prophylactic administration of ondansetron and placebo on prevention of post induction hypotension in elderly patients undergoing surgery in general anesthesia (Journal of Fatima Jinnah Medical University, 2023)
Background: Post-induction hypotension is a frequently encountered complication seen particularly in elderly population. Hypotension, by impairing vital organ perfusion, increases the morbidity and mortality of the patients. prophylactic use of ondansetron in preventing hypotension after induction of general anaesthesia in elderly patients , hence getting the benefit of preventing both hypotension and postoperative nausea and vomiting by the use of a single drug.Subjects and method: This randomized controlled clinical trial was carried out in the operation theaters of general surgery, Mayo Hospital, Lahore, from 09-09-2017 to 09-09-2018. A total of 80 patients who were to undergo general anaesthesia for elective general surgical procedures were recruited for this study. After taking informed consent, the patients were randomly divided into two groups. Patients in group A received ondansetron and those in group B received placebo prior to the induction of anaesthesia. Efficacy was labeled in terms of absence of hypotension i.e. a drop in mean arterial pressure of no more than 25% of baseline at 1, 3, 5, 9 and 11 minutes after induction of anaesthesia. The data was recorded on a predesigned proforma. Statistical analysis was done using SPSS version 21.Results: Both groups were comparable in terms of age, gender, ASA status, BMI and weight. Efficacy was seen in 19 (47.50%) cases managed by ondansetron vs. 10 (25%) in placebo group (p = 0.03). There was significant difference of efficacy in patients with age between 60 to 70 years where 63.63% patients in the Group A effectively maintained their blood pressure (p=0.02). Patients having age 70 years or above did not show statistically significant difference. History of hypertension made no impact on the efficacy of ondansetron for maintaining blood pressure after induction (p=0.53)Keywords:                       Ondansetron, Efficacy, Hypotension
Keywords: Ondansetron; Efficacy; Hypotension